Exploring the songs of Tosti, Strauss, Chausson and Jake Heggie’s Friendly Persuasions: A Homage to Poulenc (2008), including a personal interview with Jake Heggie - Jerko, Mitchell Steven (Kansas State University, 2018)
This Master’s Report extensively examines repertoire written for the lyric tenor voice. The text will explore the compositions of Francesco Paolo Tosti, Richard Strauss, Ernest Chausson, and Jake Heggie’s song cycle, Friendly Persuasions: A Homage to Poulenc. The text provides biographical information on each composer, text and translations, figures and interpretations, and some pedagogical insight. The pieces discussed are Tosti’s La Serenata, Non t’amo più, and Ideale; Strauss’s Morgen, Traum durch die Dämmerung, and Die Nacht; Chausson’s Printemps triste, Hébé, and Le temps des lilas; and Jake Heggie’s song cycle Friendly Persuasions: A Homage to Poulenc (2008). The graduate recital was presented in partial fulfillment of the requirements for the Master of Music degree in vocal performance on April 1, 2017 at Kansas State University in All Faiths Chapel. The recital featured the talents of tenor Mitchell Jerko and pianist Randall Frye.
Keywords: Jake Heggie; Friendly Persuasions: A Homage to Poulenc; Ernest Chausson; Francesco Paolo Tosti; Richard Strauss